PENINGKATAN KETERAMPILAN MENGKOMUNIKASIKAN MELALUI PERMAINAN SAINS DI KELOMPOK B RA AL-ISTIQOMAH KOTA TASIKMALAYA - Janah, Vivi Kafilatul; Mulyana, Edi Hendri; Elan, Elan (JURNAL PAUD AGAPEDIA, 2019)
ABSTRACTThis study is based ob the background behind the learning process that is less varied and the skill of communicating children is still low. Enthusiastic children to communicate what has been observed and done is still very lacking, children only communicate verbally. Though the process of communicating can be conveyed nonverbally, for example images, movements, and tables. Based on observations, the teacher also gives less opportunities for children to try and express their opinions. The media used is also very limited, so the learning process becomes less fun for children. Even though scientific learning should be a fun learning for children because children can try the media in the scientific learning activities. The purpose of this study was to improve the communication skills in class B RA Al-Istiqomah in Tasikmalaya City. This study uses Classroom Action Research (CAR). This study was conducted in three cycles using the Kemmis Mc model. Taggart. The research subjects were children of group B RA Al-Istiqomah in Tasikmalaya City totaling 16 children. The object of this research is the skill to communicate. Rainbow Water science games are games used in learning to improve communication skills. Data collection techniques use documentation and documentation, while data analysis techniques use quantitative descriptive. The instrument used is a structured observation sheet with the achievement of indicators for each activity. The results of the research that have been carried out show that there is an increase in the skills of communicating through science games. This is evidenced by an increase in the ability of teachers to plan learning, the ability of teachers in the process of implementing learning through science games from each cycle. The final result of the skill in communicating the child is in good criteria, the end result of the teacher's ability to plan learning is in very good criteria, and the end result of the teacher's ability to carry out the learning is in very good criteria.Â ABSTRAKPenelitian ini di latar belakangi dari proses pembelajaran yang kurang variatif dan keterampilan mengkomunikasikan anak masih rendah. Antusias anak untuk mengkomunikasikan apa yang telah diamati dan dilakukannya masih sangat kurang, anak hanya mengkomunikasikan dengan cara verbal. Padahal proses mengkomunikasikan dapat disampaikan secara nonverbal, misalnya gambar, gerakan, dan tabel. Berdasarkan pengamatan, guru juga kurang memberi kesempatan anak untuk mencoba dan mengeluarkan pendapatnya. Media yang digunakan juga sangat terbatas, sehingga proses pembelajaran menjadi kurang menyenangkan bagi anak. Padahal seharusnya pembelajaran saintifik merupakan pembelajaran yang menyenangkan bagi anak karena anak dapat mencoba media dalam kegiatan pembelajaran saintifik tersebut. Tujuan penelitian ini adalah untuk meningkatkan keterampilan mengkomunikasikan di kelas B RA Al-Istiqomah Kota Tasikmalaya. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK). Penelitian ini dilaksanakan sebanyak tiga siklus dengan menggunakan model Kemmis Mc. Taggart. Subjek penelitian adalah anak kelompok B RA Al-Istiqomah Kota Tasikmalaya yang berjumlah 16 anak. Objek penelitian ini adalah keterampilan mengkomunikasikan. Permainan sains Rainbow Water adalah permainan yang digunakan dalam pembelajaran untuk meningkatkan keterampilan mengkomunikasikan. Teknik pengumpulan data menggunakan dokumentasi dan dokumentasi, Sedangkan teknik analisis data menggunakan deskriptif kuantitatif. Instrument yang digunakan berupa lembar observasi terstruktur dengan capaian indikator setiap kegiatannya. Hasil penelitian yang telah dilaksanakan menunjukkan bahwa adanya peningkatan keterampilan mengkomunikasikan melalui permainan sains.